Left Atrial Myxoma - A Case Report - Otljanska, Magdalena; Boshev, Marjan (MedCrave, 2016)
Cardiac tumours are rare in cardiovascular pathology but myxomas are the most common primary cardiac tumours, frequently found in left atrium, affected more women. Clinical presentation ranges from non specific symptoms to symptoms depending on size, location and mobility of the tumour. We present a case of asymptomatic left atrial myxoma in 50 years old female patient which was incidental finding. During the hospitalization we performed many investigations to confirm the diagnosis: ECG, laboratory examination, transthoracic echocardiography (TTE), transesophageal echocardiography (TEE), as well as coronary angiography. After confirming the diagnosis of cardiac tumour we transferred the patient to a surgical centre for further treatment. Pathohistological results after surgical removal of the tumour confirmed the diagnosis of cardiac myxoma. One year follow-up by echocardiography control showed that there are no signs of tumour recurrence and patient feels well.
Keywords: atrial myxoma